2014
DOI: 10.1513/annalsats.201402-090aw
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Peptide Immunotherapy in Allergic Airways Disease

Abstract: Allergen immunotherapy with whole proteins is clinically efficacious but requires a protracted treatment period because of frequent allergic adverse events. A combination of duration of treatment and adverse events leads to poor compliance. Short synthetic peptides containing the major immunodominant T cell epitopes of allergenic proteins have been shown to reduce IgE cross-linking ability, thereby leading to fewer allergic adverse events following their administration to patients with allergies. Peptide immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 33 publications
0
35
1
Order By: Relevance
“…Early Fel d 1‐specific T‐cell activation was followed by full T‐cell unresponsiveness to allergen after 1 year in the MAT‐Fel d 1 group, characterized by increased allergen‐specific T regulatory cells, decreased circulating Fel d 1 tetramer‐positive cells, increased IL‐10 and FOXP3 expression, and change in the HR2/HR1 ratio toward HR2 . T‐cell epitope peptide immunotherapy has also significantly improved over the last years and the underlying mechanisms have been better understood …”
Section: Allergen‐specific Immunotherapymentioning
confidence: 99%
“…Early Fel d 1‐specific T‐cell activation was followed by full T‐cell unresponsiveness to allergen after 1 year in the MAT‐Fel d 1 group, characterized by increased allergen‐specific T regulatory cells, decreased circulating Fel d 1 tetramer‐positive cells, increased IL‐10 and FOXP3 expression, and change in the HR2/HR1 ratio toward HR2 . T‐cell epitope peptide immunotherapy has also significantly improved over the last years and the underlying mechanisms have been better understood …”
Section: Allergen‐specific Immunotherapymentioning
confidence: 99%
“…179181 Trials of other peptide therapies related to house dust mite, grass pollen, and ragweed are ongoing. 182,183 Nonetheless, the challenges are considerable in terms of optimizing dosing and selecting those peptide combinations that might prove efficacious within the general population. Indeed, early studies of cat peptides demonstrated their ability to induce a marked decrease in FEV 1 in asthmatic patients with cat allergy several hours after injection.…”
Section: Future Directions and Clinical Implicationsmentioning
confidence: 99%
“…Taken together, the results could explain how IgE antibodies are relevant to the process and that locally accumulating T cells could be a target for peptide immunotherapy. 35 …”
Section: Understanding the Role Of Allergens In Asthmatic Patients Anmentioning
confidence: 99%